The Significant and the Insignificant : Five Studies in Herodotus' View of History - de, Veen, J.E. van, (Amsterdam Studies in Classical Philology ;, 1996)
Although it is widely recognised that Solon's thoughts on human life (1.30-32) are important to a correct understanding of Herodotus' work, little attention has been given to their narratological meaning. On the basis of a careful interpretation of five episodes, this monograph argues that Solon's advice, 'look to the end', establishes the viewpoint from which Herodotus' stories are to be understood. This viewpoint leads to surprising conclusions as to what is and is not important to the development of history. It casts doubts especially on the magnificent role of Athens and its democracy.